[Spectral domain optical coherence tomography in the treatment of myopic choroidal neovascularization]. - Fischer, MD; Inhoffen, W; Ziemssen, F (2012)
Spectral domain optical coherence tomography (SD-OCT) investigations provide additional information about the morphological characteristics of myopic choroidal neovascularization (mCNV). Reproducible measurements of intraretinal and subretinal fluid are of growing importance for an evaluation of progression. The non-invasive technique reduces the need for frequent fluorescence angiography after individual assessment. Appropriate correction of the reference arm is mandatory. Automatic adjustment of transversal measured values due to alterations in the paraxial field (depending on the axial length) has been implemented in a new device. Mirror artefacts and excess curvature can be avoided by reducing the length of the OCT cross-section (15°). New possibilities to record the choriocapillaris and choroid have expanded the knowledge of potential pathomechanisms and risk factors.